CONTENT OF SOME ANTIOXIDANTS IN THE FRUITS OF AUTOCHTHONOUS APPLE VARIETIES - Selamovska, Ana; Viktor Gjamovski, Milena Taseska-Gjorgjijevski, Dusko Nedelkovski, Katerina Bandjo Oreshkovikj (ECO-CONFERENCE, ECOLOGICAL MOVEMENT OF NOVI SAD, 2022)
Abstract The content of vitamin C, total phenols, anthocyanins, flavan-3-ols and the antioxidant fruit activity of 7 apple varieties (Ubavo cvetka, Shareno blago, Prespanka, Tetovka, Karapasha, Kozharka, Bela Tetovka) were examined. Most of the autochthonous varieties had better properties and higher antioxidant activity compared to the standard variety Idared. The autochtho nous variety Bela tetovka had the highest content of total phenols (7544.59 mg/kg FW), flavan 3-ols (1019.957 mg/kg FW) and antioxidant fruit activity (87.2% inhibition). A positive corre lation was found between total phenols and flavan-3-ols with the antioxidant activity, as well as between flavan-3-ols and phenols. Moderate negative correlation was detected between the content of vitamin C and flavan-3-ols.
Keywords: Keywords: vitamin C, total phenols, anthocyanins, flavan-3-ols, antioxidant activity